2014
DOI: 10.3109/00365513.2014.926563
|View full text |Cite
|
Sign up to set email alerts
|

Management of severe in-patient hyponatraemia: An audit in two teaching hospitals in Yorkshire, UK

Abstract: Severe hyponatraemia is associated with significant morbidity and mortality. Drug-induced hyponatraemia was the most common aetiology observed in our group of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…However, hepcidin levels determined by this assay correlated significantly with hepcidin-25 determined by mass spectrometry in the study by Dahlfors and co-workers [ 27 ]. Due to cross-reactivity with hepcidin-20 and -22, the level of hepcidin was approximately 30% higher when hepcidin was analysed using the ELISA assay compared to the level using hepcidin-25 specific mass spectrometry [ 27 ]. Although not specific for hepcidin-25, the mean hepcidin level was significantly lower in subjects with ID compared to healthy controls using this ELISA assay [ 27 ].…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…However, hepcidin levels determined by this assay correlated significantly with hepcidin-25 determined by mass spectrometry in the study by Dahlfors and co-workers [ 27 ]. Due to cross-reactivity with hepcidin-20 and -22, the level of hepcidin was approximately 30% higher when hepcidin was analysed using the ELISA assay compared to the level using hepcidin-25 specific mass spectrometry [ 27 ]. Although not specific for hepcidin-25, the mean hepcidin level was significantly lower in subjects with ID compared to healthy controls using this ELISA assay [ 27 ].…”
Section: Discussionmentioning
confidence: 76%
“…In contrast to the ELISA developed by Butterfield and co-workers. [ 26 ], the competitive ELISA assay used in this study is not specific for hepcidin-25 [ 27 ], but it cross-reacts with hepcidin-20 and -22. However, hepcidin levels determined by this assay correlated significantly with hepcidin-25 determined by mass spectrometry in the study by Dahlfors and co-workers [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have found that adrenal insufficiency is not always considered as a cause of hyponatraemia [6] , [7] . Analysis of data from our second gather is in keeping with this statement; we found that for patients with severe hyponatraemia, only 42% had a serum cortisol measurement within two weeks of the initial finding of hyponatraemia.…”
Section: Discussionmentioning
confidence: 98%
“…Clinical practice guidelines on hyponatraemia advise that primary or secondary adrenal insufficiency should always be considered as a potential cause of hyponatraemia [5] . Despite this advice to measure serum cortisol in hyponatraemic patients, recent audits suggest that this is infrequently done [6] , [7] . We have analysed a large dataset to investigate the frequency of cortisol requesting in patients with severe hyponatraemia, and to determine the relative frequency of adrenal insufficiency in this cohort.…”
Section: Introductionmentioning
confidence: 99%